منظمات الاداء العالي بحث أستطلاعي في الشركة العامة للصناعات الجلدية والشركة العامة لتصنيع الحبوب - الطائي علي حسون (Journal of Economics and Administrative Sciences, 2008)
This study discussed modern variable in the organizational thought that is the high performance organizations in the two of Iraqi public organizations. The aim of study determines to know the level of the performance in this organizations (high or not). The data was Collected by questionnaire which contain (8) characteristics, the organizational design, strategy, process, technology, leadership, the roles, culture, and external environment). The sample contain from (76) employees; Results points that the two organizations didn’t reach to the high level of performance, and there are significance’s difference among them.